The Influence of Autocratic Leadership Style and Non-Physical Work Environment on Job Satisfaction of Ambon City Transportation Service Employees - Rehatta, Pieter NR; Wenno, Meiske; Aponno, Marlen (ProBisnis : Jurnal Manajemen, 2024)
dhdh